2010
DOI: 10.1111/j.1470-6431.2009.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer voices: adoption of residential energy‐efficient practices

Abstract: The purpose of this research is to identify constraining variables that may impinge on adopting energy-efficient practices, materials, equipment and technology in households. The intent is to uncover relationships of attitudes, beliefs, knowledge and other resource constraints to: (1) existing housing adaptations and adjustments for energy efficiency; and (2) more efficient use of energy in homes. A second objective is to identify existing practices used to reduce energy use and the adaptations made to the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 7 publications
2
37
0
1
Order By: Relevance
“…Studies from Sweden (Nair et al 2010), the USA (Niemeyer 2010) and Germany (Achtnicht 2011) replicate this perspective, although Achtnight highlights the potential importance for climate change as a driving factor. Given that climate change awareness as a factor for adoption is partially driven by income and education (Semenza et al 2008), it seems that Chahal's (2012) assertion that it does not drive adoption in UK social housing is potentially supported.…”
Section: The Adoption Of Energy Efficient Measuresmentioning
confidence: 73%
“…Studies from Sweden (Nair et al 2010), the USA (Niemeyer 2010) and Germany (Achtnicht 2011) replicate this perspective, although Achtnight highlights the potential importance for climate change as a driving factor. Given that climate change awareness as a factor for adoption is partially driven by income and education (Semenza et al 2008), it seems that Chahal's (2012) assertion that it does not drive adoption in UK social housing is potentially supported.…”
Section: The Adoption Of Energy Efficient Measuresmentioning
confidence: 73%
“…Supporters of CBSM theory have confirmed the importance of strategies such as prompts, feedback, social support and public commitment as key drivers that foster behavioural change. Some examples of studies that support this view are: 1) recycling and purchasing items with minimal packaging (Cole & Fieselman, 2013;Haldeman & Turner, 2009;Hughes, 2012); 2) turning off unnecessary heating or cooling (Kaiser & Schultz, 2009;Niemeyer, 2010;Petersen, Shunturov, Janda, Platt, & Weinberger, 2007); 3) using public transport instead of private vehicles (Grob, 1995;Stein, 2004); and 4) water conservation (Beal, Stewart, & Fielding, 2013).…”
Section: Community-based Social Marketing Theorymentioning
confidence: 99%
“…Similarly, Niemeyer [18] found that householders least likely to act to reduce greenhouse gas emissions hold lower pro-environmental attitudes and less concerns about, and knowledge of, environmental issues. Due to these financial constraints and motivations, low income householders are more likely to adopt curtailment behaviour, involving repetitive efforts to reduce energy use [19].…”
Section: Conceptual Framework and Methodologiesmentioning
confidence: 99%